Private action in public interest - Luo, Jiao; Kaul, Aseem (Strategic Management Journal, 2019)
[Research Summary: We develop a theoretical framework to define the comparatively efficient organizational form for dealing with a social issue, based on the market frictions associated with it. Specifically, we argue that for-profits have an advantage in undertaking innovation and coordinating production economies, nonprofits in playing a fiduciary role given ex post information asymmetry, self-governing collectives in dealing with bounded externalities through private ordering, and state bureaucracies in governing general externalities. We build on these arguments to develop a mapping between combinations of these market frictions and the comparatively efficient arrangements to govern them, including a variety of hybrid arrangements such as private-public partnerships, social enterprises, corporate social responsibility, and so on. Our framework thus contributes to research in strategy, organizations, and public policy. Managerial Summary: What is the best way to deal with a social problem? While some believe such problems are best left to the state, others argue that business should take the lead in solving them, or favor nonprofit solutions. In this article, we move beyond such one-size-fits-all approaches, highlighting the different strengths of different organizational forms. We argue that for-profits' strong incentives make them more innovative; nonprofits are more trustworthy in representing the best interests of others; collectives enable actors to self-organize around a common interest; and the state is best for issues that impact the entire population. We thus develop a mapping between the nature of the social problem and the organizational form—or combination of organizational forms—that may deal with it most efficiently.]